Risk factors for acute pulmonary edema after adenotonsillectomy in children - Nuntigar Sonsuwan (2018)
Objective: Adenotonsillectomy is a common surgical procedure in children. Acute pulmonary edema after this procedure is a rare complication but may be fatal. The factors associated with pulmonary edema after adenotonsillectomy were studied. Methods: All consecutive patients with an age of less than 15 years who underwent adenotonsillectomy at Chiang Mai University Hospital were enrolled. The study period was from January 2004 to December 2008. Clinical factors were retrospectively retrieved from medical records. Factors associated with acute pulmonary edema after adenotonsillectomy were computed using multiple logistic regression analysis. Results: There were 216 patients who underwent adenotonsillectomy due to airway obstruction during the study period. Five patients were excluded due to incomplete data. Of those included, 129 patients (61.1%) were male with mean age of 6.6 (SD 3.2) years. Four significant factors associated with the development of post-operative pulmonary edema after the adenotonsillectomy were procedure, age, obesity, and pulmonary hypertension. Conclusion: Factors associated with acute pulmonary edema after adenotonsillectomy in children were adenotonsillectomy procedure, young age, obesity, or having pulmonary hypertension. Clinicians should be aware of these risk factors while performing adenotonsillectomy in children. © 2014 Elsevier Ireland Ltd.